HOW STRONGLY DO HEDONISM AND SOCIAL VALUES INFLUENCE CONSUMERS' ATTITUDES AND PURCHASE INTENTION? EMPIRICAL EVIDENCE FROM VOSCO COFFEE - Rohima, Rohima; Anjaningrum, Widiya Dewi (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
Indonesia has achieved fourth in the global coffee production ranking, witnessing a 4.04% rise in coffee consumption, reaching an unprecedented level of 5 million bags (60 kg each) in 2020/2021. This surge has attracted numerous young entrepreneurs to the thriving coffee industry, especially in the burgeoning coffee shop sector. Cities such as Jakarta, Surabaya, and Medan, as well as educational hubs like Malang, are experiencing a proliferation of coffee establishments, creating new opportunities for the industry. This research aims to thoroughly assess how hedonism and social values influence customer attitudes and purchasing intentions, with a detailed examination of the mediating role of customer attitudes. The study focuses on Vosco Coffee consumers in Malang, with a carefully selected sample of 180 respondents using accidental sampling technique. Quantitative data collected through well-designed questionnaires underwent rigorous analysis using the Partial Least Square (PLS) method. The empirical findings emphasize that hedonism and social values directly, positively, and substantially impact consumer attitudes and purchase intentions. Notably, a resilient customer attitude significantly enhances purchasing intentions. This study encourages future researchers to conduct more comprehensive investigations into the factors shaping consumer attitudes and purchase intentions in this context.Keywords: Hedonism, Social Value, Consumer’s Attitude, Purchase Intention